Katekese Gereja Katolik Tentang Perkawinan Berciri Monogami Dan Seumur Hidup Menurut Kitab Kanonik Kan, No. 1056 - Aman, Aman; Endi, Yohanes (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2023)
The focus of this paper is to discuss the catechesis of the Catholic Church on marriagecharacterized by monogamy and lifelong according to the Code of Canon Law, No. 1056. In essence, marriage has the characteristics of being sacred, monogamous, and lifelong. These characteristics or traits of marriage are not only owned by the Catholic Church, but all religions in the world have the same characteristics. The author argues that the main causes of marital disharmony are breaking marital vows and not forgiving each other. The Catholic Church reiterates that if there is a misunderstanding from one of the spouses, they should forgive, love and forgive each other. Jesus Christ himself has taught to forgive each other, but the Catholic faithful cannot live and follow the example of Jesus Christ. The two methodologies used in writing this article are phenomenological and text analysis. In understanding the characteristics of marriage in the Catholic Church, the author uses Scripture, the Church document Gaudium Et Spes, the Familiaris Consortio document, the magisterium: Encyclical Humanae Vitae, and the Code of Canon Law. In addition, the author uses references from books and journals that are directly related to the theme of this article. The findings conveyed from the writing of this article are that it contains an invitation, namely how to live a marriage characterized by monogamy (unitas) and for life. Indeed, these characteristics of marriage have been written in the Old Testament (OT) and fulfilled by Jesus in the NT. So man cannot deny the statements of the Holy Scriptures and it has become the law of his nature. The author affirms that a valid and normal Catholic marriage is between a man and a woman. Key Words: Marriage; Catholic Marriage; Monogamy; Lifetime